Surveillance of infectious diseases in the Arctic. (August 2016) - Bruce, M.; Zulz, T.; Koch, A.
Abstract: Objectives: This study reviews how social and environmental issues affect health in Arctic populations and describes infectious disease surveillance in Arctic Nations with a special focus on the activities of the International Circumpolar Surveillance (ICS) project. Methods: We reviewed the literature over the past 2 decades looking at Arctic living conditions and their effects on health and Arctic surveillance for infectious diseases. Results: In regards to other regions worldwide, the Arctic climate and environment are extreme. Arctic and sub-Arctic populations live in markedly different social and physical environments compared to those of their more southern dwelling counterparts. A cold northern climate means people spending more time indoors, amplifying the effects of household crowding, smoking and inadequate ventilation on the person-to-person spread of infectious diseases. The spread of zoonotic infections north as the climate warms, emergence of antibiotic resistance among bacterial pathogens, the re-emergence of tuberculosis, the entrance of HIV into Arctic communities, the specter of pandemic influenza or the sudden emergence and introduction of new viral pathogens pose new challenges to residents, governments and public health authorities of all Arctic countries. ICS is a network of hospitals, public health agencies, and reference laboratories throughout the Arctic working together for the purposes of collecting, comparing and sharing of uniform laboratory and epidemiological data on infectious diseases of concern and assisting in the formulation of prevention and control strategies (Fig. 1). In addition, circumpolar infectious disease research workgroups and sentinel surveillance systems for bacterial and viral pathogens exist. Conclusions: The ICS system is a successful example of collaborative surveillance and research in an extreme environment.